Physics Teacher Training in Chile: Reality and Challenges - Carla Hernández Silva; Yadrán Gómez-Martínez; Damián Ruz López; Mauricio Silva Ugalde; Silvia Tecpan Flores (Universidad Autónoma de Baja California, 2020)
The lack of physics teachers in Chile has been a cause for concern for the last 15 years. This study aims to identify and describe the key features of current physics teacher training programs in universities in the Council of Rectors of Chilean Universities (CRUCH). This descriptive and ex post facto research employs historical data analysis and qualitative analysis techniques. The main findings include a geographic centralization and gender gaps in enrollment and graduation rates. The physics and education courses appear to run parallel and feature in similar proportions, suggesting a dissociation between the two areas. The implications for teacher training programs are discussed and lines of action for future research are proposed based on the findings.